2020
DOI: 10.1038/s41467-020-15506-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapause surface wave oscillates the magnetosphere and diffuse aurora

Abstract: Energy circulation in geospace lies at the heart of space weather research. In the inner magnetosphere, the steep plasmapause boundary separates the cold dense plasmasphere, which corotates with the planet, from the hot ring current/plasma sheet outside. Theoretical studies suggested that plasmapause surface waves related to the sharp inhomogeneity exist and act as a source of geomagnetic pulsations, but direct evidence of the waves and their role in magnetospheric dynamics have not yet been detected. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(97 citation statements)
references
References 77 publications
(99 reference statements)
7
90
0
Order By: Relevance
“…The strong similarities shown by the surface waves near the plasmapause and the K-H waves near the magnetopause demonstrate the coupling of these waves via the eigenfrequency of the NEPS resonator (Mazur & Leonovich, 2006). The surface waves near the plasmapause were first identified by He et al (2020) as plasmapause surface waves. In this study, according to our specification, these plasmapause surface waves appeared in the hot zone.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The strong similarities shown by the surface waves near the plasmapause and the K-H waves near the magnetopause demonstrate the coupling of these waves via the eigenfrequency of the NEPS resonator (Mazur & Leonovich, 2006). The surface waves near the plasmapause were first identified by He et al (2020) as plasmapause surface waves. In this study, according to our specification, these plasmapause surface waves appeared in the hot zone.…”
Section: Discussionmentioning
confidence: 98%
“…As depicted by global auroral pictures, taken by the Defense Meteorological Satellite Program (DMSP) satellites in the topside ionosphere, large‐scale auroral undulations appear with amplitudes (∼40–400 km) and wavelengths (∼200–900 km), which are comparable, and can persist for up to 3.5 h (Lui et al., 1982; Nishitani et al., 1994). Large‐scale auroral undulations are also called sawtooth aurora (He et al., 2020) and giant undulations (Henderson et al., 2010). Typical features, which are consistent with the DMSP photographs‐shown characteristics (Lui et al., 1982), are also depicted by other types of images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also very interesting to note that Zhang et al (2005) also find that a number of detached forms were associated with large-scale undulations in the equatorward boundary of the aurora found poleward, and He et al (2020) have recently shown that such auroral structuring is associated with actual structuring of the equatorial plasmapause. He et al (2020) also demonstrated that energetic electron and proton populations intrude into the low density regions which could be scattered to produce auroras.…”
Section: Detached Subauroral Patchesmentioning
confidence: 94%
“…The nighttime ionospheric disk image can be used to investigate the structure and Optical Remote Sensing of Planetary Space Environment DOI: http://dx.doi.org/10.5772/intechopen.98427 evolution of equatorial ionization anomaly [25]. The auroral image can be used to manifest the thermal plasma transportation in the Earth's magnetosphere and to denote the substorm activity in Earth's space [26]. The plasmaspheric images can be used to characterize the large-scale convections in the Earth's magnetosphere [27,28].…”
Section: Optical Remote Sensing Images Of Planetary Spacementioning
confidence: 99%